1991
DOI: 10.1002/jso.2930480311
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal sarcomas

Abstract: The clinical and pathologic characteristics of five patients with esophageal sarcomas are presented, including the only recorded esophageal Triton tumor (malignant schwannoma), the third recorded synovial sarcoma, two patients with carcinosarcoma, and one with leiomyosarcoma. All five patients were males who presented with dysphagia. Three tumors were in the cervical esophagus, and the remaining two were in the distal esophagus. On endoscopic examination, three of the tumors were noted to be polypoid, while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
30
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 21 publications
0
30
0
1
Order By: Relevance
“…The recognition of SS in this unexpected site is probably often mistaken. Cytogenetic approach with fluorescence in situ hybridization (FISH) showing t(X; 18) translocation in SS is then crucial for allowing the diagnosis [21]. We report a case of primary SS of the esophagus, for which the diagnosis suspected histologically was made by cytogenetic studies.…”
mentioning
confidence: 99%
“…The recognition of SS in this unexpected site is probably often mistaken. Cytogenetic approach with fluorescence in situ hybridization (FISH) showing t(X; 18) translocation in SS is then crucial for allowing the diagnosis [21]. We report a case of primary SS of the esophagus, for which the diagnosis suspected histologically was made by cytogenetic studies.…”
mentioning
confidence: 99%
“…In general, enucleation of submucosal esophageal tumors seems reasonable, except for patients with suspected malignancy. In our case, the Ivor Lewis procedure was selected for complete resection of the tumor, as preoperative findings suggested leiomyosarcoma and complete resection would thus facilitate long-term survival [18,19]. In our review, one patient with a preoperative diagnosis of malignant schwannoma underwent esophagectomy.…”
Section: Discussionmentioning
confidence: 97%
“…Radiotherapy may be used as adjuvant treatment, in cases where the risk of local recurrence is considered to be high, for example, in high-grade tumors, or when limb preservation is important. Limited surgery may be used to avoid amputation or the excessive loss of tissue, followed by radiotherapy in order to sterilize the remaining malignant cells (21)(22)(23)(24). It has been reported that completely resected lowgrade soft-tissue tumors do not require additional treatment (25).…”
Section: Discussionmentioning
confidence: 99%
“…However, due to its rarity, it is difficult to determine a pre-operative diagnosis and appropriate treatment strategy for cases of esophageal leiomyosarcoma. In previous years, leiomyosarcoma was not considered to be sensitive to radiation; therefore, radical radiotherapy treatment was rarely administered and a limited number of reports regarding the use of radiotherapy in the treatment of leiomyosarcoma exist in the literature (6,24,28). Although leiomyosarcoma has poor sensitivity to radiation, the tumor may be effectively controlled by increasing the radiation dose appropriately.…”
Section: Discussionmentioning
confidence: 99%